The Effect of Visual, Auditory, Kinestic Learning Styles on Student Learning Outcomes in Science Subjects - Arni, Yusni; Utami, Widya Wuri; Khoirunnisak, Lisma; Amelia, Frizka (Journal Of Education And Teaching Learning (JETL), 2024)
This study was conducted with the aim to evaluate and determine the effect of visual, auditory, kinesthetic learning styles on student learning outcomes in science learning at SD Negeri 244 Palembang. This study is a quantitative research that uses an experimental method with a type of Quasi-Experimental experimental design. The variables to be studied consisted of visual, auditory, kinesthetic learning styles (X), and student learning outcomes which became the dependent variable (Y). All students in grades I - VI of SD Negeri 244 Palembang are the research population and there are 40 students who are the samples in this study. Information collection methods applied questionnaires and documentation. Questionnaire was used as a tool to identify visual, auditory, and kinesthetic learning styles. Based on the results of the t test with a significance level of 0.000 which is lower than the t table value of 2.023, it can be concluded that there is a significant effect of visual, auditory, kinesthetic learning styles on student learning outcomes in science learning at SD Negeri 244 Palembang.